Novel properties of 0D metal–organic polyhedra bonded to the surfaces of 2D graphene and 1D single-walled carbon nanotubes. Issue 25 (7th June 2017) - Kumar, Ram; Rao, C. N. R.
Abstract : Stabilization of individual 0D metal–organic polyhedra (MOP) on 2D graphene and 1D single-walled carbon nanotube (SWNT) surfaces results in a significant improvement of porosity, surface area and catalytic activity of the composites. Abstract : A strategy for the stabilization of metal–organic polyhedra (MOP) cages on graphene (Gr) and single-walled carbon nanotubes (NT) is reported. The surface area of the composites, MOPGr and MOPNT increases by an order of magnitude with a significant increase in pore volume in comparison to bulk MOP. The composites show an enhancement in the catalytic activity of up to ∼80% relative to bulk MOP in the conversion of propylene oxide into propylene carbonate. Depositing individual MOP cages on graphene or SWNT surfaces is beneficial in terms of gas adsorption and catalytic properties and provides a good example for useful effects of bonding materials of different dimensionalities.